Struktura sorevnovatel'noj dejatel'nosti sportsmenovvysokoj kvalifikacii v raznyh versijah bokserskih turnirov - Berinchik, D.; Lysenko, O. (Science in Olympic Sport, 2018)
Objective. To identify the differences in the structure of competitive activity of elite athletes competing in different versions of boxing tournaments. Methods. An analysis of the official protocols of boxing matches was carried out to identify the leaders in the middleweight category among amateurs, semi-professionals, and professionals based on the results of the performance of the athletes. When analyzing video records of matches, the notation system was used for recording the bouts with the scores characterizing competitive performance and activity of an athlete as well as diversity of his actions. Results. The differences were identified in the structure of competitive activity of semi-professional (WSB) and professional boxing compared to amateur boxing as the initial stage in the development of professional career of high-class boxers. Professional boxers showed a markedly high density of the bout and a level of activity in the bout, which is expressed in greater diff erences when compared to both amateur boxers (15.96-107.39 %) and semi-professional boxers (8.71-37.85 %). The differences between qualified amateur boxers and semi-professionals were smaller and ranged from 6.67 to 9.58 %. It is noticeable that more successful boxers of a high class, above all, are distinguished by the higher competitive performance due to having more punches that reached the target. Conclusion. The current trends in improving the system of sports training consist in the need to bring it in line with the rules of diff erent versions of boxing matches. The evolution of modern boxing has demonstrated a tendency for the changes in the rules of boxing matches towards an increase in the number of rounds with a duration of 3 minutes from three to five, which is accompanied by a further increase in the intensity of the boxers actions as well as a growth of the effectiveness of their technical and tactical actions in all rounds of the bout.